Efficient Analytical Pretreatment of Cr(VI) in Ethylene Wastewater by Grafting g-C3N4 Material Based on Coupling Agent-Modified Basalt Matrix (Basalt–MTES/g-C3N4) - Zheng Wang; Mingchang Jia; Yi Ren; Hongmin Ren; Shuhao Liang; Jiaru Sun; Siqi Hao; Jinchuan Li; He Li (Molecules)
This study presents a novel Basalt-based grafted graphitic carbon nitride composite (Basalt–MTES/g-C3N4) for the efficient pretreatment of Cr(VI) in ethylene wastewater. The composite was synthesized by the acid purification of natural Basalt, surface modification with hydroxymethyl triethoxysilane (MTES), and the subsequent grafting of g-C3N4. Characterization confirmed the uniform distribution of nano-sized g-C3N4 particles on a Basalt surface with intact chemical bonding, where 82.63% of melamine participated in g-C3N4 crystallization. The material exhibited a high specific surface area (403.55 m2/g) and mesoporous structure (34.29 nm). Acidic conditions promoted the protonation of amino groups in g-C3N4, significantly enhancing Cr(VI) adsorption via ion exchange. Adsorption kinetics followed the pseudo-second-order model, while isotherm data fitted the Langmuir monolayer adsorption mechanism. The composite achieved 97% Cr(VI) recovery through chromatographic extraction and retained 96.87% removal efficiency after five regeneration cycles. This work demonstrates a cost-effective, recyclable green pretreatment material for high-sensitivity Cr(VI) monitoring in ethylene industry wastewater, offering dual benefits in environmental remediation and regulatory compliance. The design synergizes natural Basalt’s stability with g-C3N4’s adsorption affinity, showing practical potential for sustainable wastewater treatment technologies.